Teacher accountability, datafication and evaluation: A case for reimagining schooling - Holloway, Jessica (Education Policy Analysis Archives, 2020)
The purpose of this commentary is to push the boundaries (real and perceived) of how we think about teacher accountability, education and the purpose of schooling in contemporary times. It takes as a starting point a view that recent changes to the Every Student Succeeds Act does little to shift the underpinning logics of high-stakes teacher accountability that ultimately threaten the stability and adaptability of public schools. Building from this presumption, it explores more universal features of contemporary schooling practices (e.g., standardization, datafication and evaluation) that undermine teacher expertise, autonomy and professional discretion. The purpose is to provide a new lens for thinking about the role of education and to radically disrupt the ‘norms’ we have come to accept as necessary features of modern schooling. Ultimately, it serves as a thought experiment to provide some space for imagining new possibilities and thinking “outside of” the traditional accountability “box”.